Anthropocentrism and Environmental Crisis in Hujan Novel by Tere Liye: An Ecocritical Study of Human-Induced Environmental Damage - Romdoni, Muhamad Rizky (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This study aims to reveal how human actions impact environmental damage as depicted in the novel Hujan by Tere Liye. The research design used a qualitative method, equipped with an ecocriticism theory of Anthropocentrism by Greg Garrard to explore the anthropocentrism in the novel. The results show; 1) The environmental damage: different kinds of environmental harm, including pollution, apocalypse, dwelling, and earth, with humans as the main cause and the impact that causes the ecosystem damage which eventually leads to extinction; 2) The environmental abuse: the role of humans in the destruction of the environment is reflected in the actions of destroying nature carried out by humans on the basis of the anthropocentrism paradigm; 3) The ecological ethics: the novel highlights the critical need for adhering to environmental wisdom, which includes maintaining harmony with nature, adopting sustainable practices, and considering long-term consequences of human actions.environmental values are embodied in the novel following the principles of environmental ethics.